States and transitions in aspen dominated ecosystems in western Colorado - Dickey, Christopher Patrick King, author; Meiman, Paul, advisor; Fernandez-Gimenez, Maria, advisor; Melzer, Susan, committee member; Shepperd, Wayne, committee member (Colorado State University. Libraries, 2017)
In Colorado and the southwestern United States, quaking aspen (Populus tremuloides Michx.) is a species of high ecological, economic, and aesthetic importance. In response to the interests of several landowners and land managers in my study sites, this thesis describes my efforts to identify differences among aspen stand types in western Colorado and the ecological sites on which they occur; to describe aspen communities on different ecological sites based on species composition, functional traits, and drivers of change; and to synthesize this information in state-and-transition models (STM) applicable to specific ecological sites (ESs). In Chapter 2, I analyzed the results of aspen inventories and found that three of my four study sites contained aspen stands that are considered stable aspen subtypes. The fourth site contained stands representing a seral aspen type where conifer encroachment has occurred. I found higher frequencies and intensities of browsing in areas with isolated stands compared to areas with large continuous stands and in these areas there was evidence that browsing has affected juvenile aspen stem densities. Clear-felling on one site with large stable stands stimulated new stem growth, while prescribed burns on another site with smaller stable stands did not stimulate new stem growth. In Chapter 3, I classified sites based on soil and other abiotic site characteristics using partitioning around medoids (PAM). I then developed STMs for these sites using agglomerative hierarchical clustering analysis, indicator species analysis, permutational multivariate analysis of variance (PERMANOVA), non-metric multidimensional scaling (NMS), and the Random Forest algorithm to identify plant species associations and correlated abiotic factors and management treatments. Three of my STMs depict aspen and non-aspen dominated states associated with differences in abiotic site characteristics, and one STM depicts a single aspen dominated state. My investigation of aspen health and factors contributing to aspen mortality provides land managers in western Colorado with useful information for making informed decisions regarding aspen management. The STMs I have developed for these sites show which abiotic variables can be expected to be correlated with specific vegetation states and will inform future STM development for aspen-dominated systems. My findings suggest that the frequency and intensity of herbivory has played a major role in aspen survival at three of my four study sites. Future work is needed to develop more complete STMs for aspen-dominated systems in western Colorado.